Name Changes in Common Indian Grasses - Raizada, M. B. (Indian Forester, 1959)
This paper gives the up-to-date correct botanical names, in accordance with the latest International Code of Botanical Nomenclature of about 425 species of Indian grasses. Immediately below the correct names are given important Synonyms. To facilitate easy reference the list has been arranged alphabetically and an index provided at the end so that workers acquainted with more familiar names, commonly in use at present, may be able to trace easily the correct names.